Waterpipe device cleaning practices and disposal of waste associated with waterpipe tobacco smoking in homes in the USA. (20th July 2019) - Kassem, Nada OF; Kassem, Noura O; Liles, Sandy; Reilly, Erin; Kas-Petrus, Flora; Posis, Alexander Ivan B; Hovell, Melbourne F
Abstract : Objectives: To quantify postsmoking waterpipe tobacco (WPT) waste and describe postsmoking waterpipe (WP) device cleaning practices and disposal of associated waste in home settings. Methods: We analysed data from a US convenience sample of 50 exclusive WPT smokers, mean age 25.3 years. Data were collected at a home visit during which participants smoked one WPT head and completed a self-administered questionnaire on WP cleaning practices and disposal of waste associated with WPT use. Research assistants provided and prepared a WP for participants by weighing and loading 10 g of WPT in the WP head and placing 470 mL of water in the WP bowl. At the completion of the smoking session, research assistants measured the remaining WPT and water. Descriptive analyses were performed. Results: Of the 10 g of fresh WPT used for each smoking session, 70.1% (mean=7.01 g) was discarded postsmoking as waste; for each 470 mL of water used in the WP bowl, 94.3% (mean=443 mL) was discarded. WP device cleaning practices ranged from never cleaning the device to cleaning it after each smoking session. Respondents reported discarding smoked WPT residue in the trash (81.6%) or the kitchen sink (14.3%) and discarding postsmoking charcoal in the trash (57.6%), the kitchen sink (27.3%) or backyard soil (9.1%). Respondents reported discarding smoked WP water in the kitchen sink (76.5%), bathroom sink (14.7%), toilet (2.9%) and backyard soil (5.9%). Conclusions: Interventions and regulations are needed to inform proper WP device cleaning practices and disposal of waste associated with WPT use. Trial registration number: NCT03253653 .